Environmental vulnerability analysis of high river basin san Pedro, Miranda, Venezuela - Coromoto Marín, Haideé (2017)
Environmental vulnerability by flooding and displacement of the communities located in the upper San Pedro River, Guaicaipuro, Miranda state, Venezuela was characterized using GIS. The area was divided into two parts: a slightly intervened (A) and strongly intervened (B) to obtain thematic maps used as indicators, which were standardized by re-classification technique, assigned numerical values on a scale of 1 to 5. The results show that the flood vulnerability in the sub watershed showed the following trend: middle class (3) 33.75%> class 2 (Low)31.91%> class 1 (very low) 26.86%> Class 4 (High) 6.12%> class 5 (very high) 1.37%, despite the high and very high classes correspond to communities near the river (San Pedro, Rio Arriba and Andres Bello), characterized by the presence of urban development, high agricultural activity, which suggests a high flood risk. The spatial distribution of displacement vulnerability suggests that predominates middle (3) and lower (2), which represents 50.58% and 36.25% respectively, while the rest of the upper class (4), very low (1) to very high (5) showed percentages of 9.37, 3.29 and 0.41 respectively. The classes of high and very high vulnerability are located in the area of major intervention (Zone B), with a very irregular pattern associated with steep slopes (> 30%) and soils with agricultural managements systems with few protectors crops like vegetables, where land preparation leave uncovered soil surface, favoring degradation processes and affecting the sustainability of the area. The results obtained have served to discriminate which communities are most vulnerable and establish priorities in terms of intervention to minimize environmental impacts.